Can the resource-exhausted city promotion program reduce enterprise carbon emission intensity? Evidence from China - Lin, Zhuoran; Gao, Jingyi (Frontiers in Environmental Science, 2024)
The Resource-Exhausted City Promotion (RECP) program is a significant initiative by the Chinese government aimed at fostering transformation. The RECP program constitutes a vital avenue for advancing low-carbon transformation, though its influence on microenterprises' carbon emissions and underlying mechanisms remains unexplored. We use China's industrial enterprise database from 2003 to 2014 and organize data concerning resource-exhausted cities in China. Employing the staggered Difference-in-Differences (staggered DID) method, the research investigates the impact of the RECP program on enterprise carbon emission intensity. Results show that the impact of the RECP program on enterprise carbon emission intensity is significantly negative. This effect is more significant for enterprises in areas with lower environmental protection pressure, those situated in mining cities, larger enterprises, and those exhibiting higher carbon emission intensity. Furthermore, we identify the influencing channels from the above effect as the screening effect and the tourism development level. The screening effect resulting from the exit of enterprises in highly polluting industries can exacerbate the negative impact of the RECP program on the enterprise carbon emission intensity. Meanwhile, enhancing the level of tourism in the region is a key strategy for the RECP program to further reduce the enterprise carbon emission intensity. This effect emerges as a crucial approach for reducing enterprise carbon emission intensity within the RECP program framework. The results of this study contribute to driving the implementation of such program for government and enterprises.